(untitled) (Al-Aasar, 2025)
Marriage being a Solid contract in Islam, has an objectivity, so it is understood. We cannot ignore the fact mental and physical satisfaction of the both parties is above the question. But classical scholars considered the fact that if husband’s whereabouts are not known, the woman has no right to get married again. Hanfi, Shafi and Shia jurisprudence have consensus on the above-mentioned issue but Malki devised a way for the deprived leady. This article provides difference of the opinion regarding the matter, and solution of the miss miseries of the woman who is being compelled by the jurists to live a lonely and miserable life. Inspite of being hanfi, solid opinion of Mufti Manipur Rahman is also part of the. Article.